Sistem Informasi Manajemen Klinik Untuk Pengelolaan Data Pasien dan Rekam Medis Berbasis Website Menggunakan Metode System Development Life Cycle - Sentanu, Arga Seva Amartya; Chamid, Ahmad Abdul; Fiati, Rina (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The advancement of information technology has significantly impacted the healthcare sector, particularly in patient data management and medical administration. Klinik Bidan Eny Wijaya still relies on manual methods for recording patient data, which poses risks of data entry errors and data loss. This study aims to develop a web-based Clinic Management Information System to enhance efficiency in recording, storing, and managing medical records and patient administration. The development method used is the Software Development Life Cycle (SDLC), consisting of five main stages: requirement analysis, design, implementation, testing, and maintenance. System testing was conducted using the Black Box method to ensure its functionality meets user needs. A case study was conducted at Klinik Bidan Eny Wijaya using interviews, observations, and literature studies to understand the challenges in clinic management. The system was developed using PHP programming language and MySQL database. The result of this study indicate that the developed system significantly improves efficiency in petient data recording, storage, and management of medical records and administration at Klinik Bidan Eny Wijaya.